1992
DOI: 10.1002/jcp.1041500114
|View full text |Cite
|
Sign up to set email alerts
|

Effects of pH‐variations on the kinetics of growth and energy metabolism in cultured T‐lymphoma cells: A microcalorimetric study

Abstract: The progression of T-lymphoma cells (CCRF-CEM) growing in suspension has been monitored during long term (12-28 h) batch experiments using microcalorimetry. In parallel with the calorimetric measurements, changes in cell concentration, pH, p(O2) and concentrations of the main energy sources (glucose and glutamine) were determined. The overall metabolic rate per cell (as reflected by the heat production rate per cell, Pcell) and the growth rate decreased with time. These changes could be attributed solely to th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

1995
1995
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(4 citation statements)
references
References 16 publications
(15 reference statements)
0
4
0
Order By: Relevance
“…Because metabolic heat is produced in all cellular biochemical processes, IMC measurement of exothermic heat flow rate is a general technique for studying the overall magnitude of metabolic response. [26][27][28][29][30][31][32][33][34] A general method, such as IMC, is also particularly well suited to the detection of unknown cell metabolic phenomena. [35][36][37][38][39][40][41][42] In the present study, significant heat flow rate differences were demonstrated for MØs cultured with endotoxin or particulates compared with cells cultured without artificial stimuli.…”
Section: Discussionmentioning
confidence: 99%
“…Because metabolic heat is produced in all cellular biochemical processes, IMC measurement of exothermic heat flow rate is a general technique for studying the overall magnitude of metabolic response. [26][27][28][29][30][31][32][33][34] A general method, such as IMC, is also particularly well suited to the detection of unknown cell metabolic phenomena. [35][36][37][38][39][40][41][42] In the present study, significant heat flow rate differences were demonstrated for MØs cultured with endotoxin or particulates compared with cells cultured without artificial stimuli.…”
Section: Discussionmentioning
confidence: 99%
“…Compared with differential scanning calorimeter (DSC), microcalorimeter offers a specific sensitivity that is approximately 1000 higher. For a long time, it has been used to study biological processes and molecular interactions , in life sciences. As an essential thermal analysis method, microcalorimetry was used to study the kinetics and thermodynamics of curing reaction. Compared with the traditional method, the advantage of microcalorimetry is that it can determine the thermodynamic and kinetic parameters simultaneously.…”
Section: Introductionmentioning
confidence: 99%
“…Boar and guinea pig spermatozoa can maintain motility only in the presence of O 2 , whilst human and bovine spermatozoa maintain their motility under aerobic and anaerobic conditions (Krzyzoiak et al, 1999). Thus, the metabolic efficiency of a system could be assessed from the ratio of oxygen consumed to the heat produced, in which the more efficient system displays the higher ratio (Gnaiger and Kemp, 1990;Bäckman et al, 1992).…”
Section: Introductionmentioning
confidence: 99%
“…Microcalorimetry has been an important tool for the study of metabolic activities of cells and biological tissues (Bäckman et al, 1992;Kemp and Guan, 2000;Kemp , 2001;Lee and Kaletunc, 2002). Isothermal heat rates have been measured for the intact cells by both batch and flow calorimetry and relate to such properties as growth rates, thermodynamic parameters and effects of activators (Kemp, 1991;Krzyzoiak et al, 1999;Wadsö et al, 2001).…”
Section: Introductionmentioning
confidence: 99%